Cholestatic hepatitis: atypical presentation of Epstein-Barr virus infection - Carolina Guimarães (Journal of Pediatric and Neonatal Individualized Medicine, 2018)
Epstein-Barr virus (EBV) primary infection frequently leads to a mild and self-limited increase in liver enzymes. However, clinical manifestations of hepatitis including jaundice are very rare in children. We report a case of an 11-year-old female with fever, vomiting, abdominal pain, jaundice and choluria. The physical examination showed jaundice, cervical adenopathy and mild hepatomegaly. She later developed tonsillitis and a rash. Laboratorial evaluation revealed atypical lymphocytosis (19.3%), increased aspartate aminotransferase 371 IU/L, alanine aminotransferase 373 IU/L and γ-glutamyl transpeptidase 110 IU/L, hyperbilirubinaemia (total bilirubin 14.83 mg/dL, direct bilirubin 11.39 mg/dL), bilirubinuria and hypoalbuminaemia (minimum 2.4 g/dL). The anti-EBV viral capsid antibodies IgM and IgG were positive. Other viral serologies were negative and the abdominal ultrasound was normal. EBV first infection should be considered in the differential diagnosis of cholestatic hepatitis in children.